Digital preservation and access to the South African documentary national heritage at the National Library of South Africa - Masekoameng, Clement Mahudu (My University, 2022)
Digitisation of library materials offers Library and Information Services (LIS) organisations, national libraries in particular, opportunities to preserve and manage fragile and unique materials, by protecting their physical, saving them from deteriorating and facilitating unmediated access to such collection. The aim of the study was to examine processes involved in the digitisation of the South African National Documentary and Cultural Heritage for the purpose of preservation and access at the national library of South Africa (NLSA). The study was guided by the systems theory by looking into the selection, processing and disseminating of digital records at the NLSA. The study examined adherence to the policies and national legislative frameworks, the technologies used for digitization and access to digitized collections, tools used for accessing digital collections, as well the challenges experienced in the NLSA digitization project. Qualitative research methodology was adopted, through a case-study research whereby, semi-structured interviews, document analysis and observations were triangulated as data collection methods for the study. The key findings showed that the digitisation project at the NLSA adheres to pieces of national legislation and international guidelines such as International Standards Organization (ISO), the and draft digitisation policy developed by the Department of Sports, Arts and Culture which takes into consideration the national legislative framework such as the RSA Constitution, the NLSA Act, the Legal Deposit Act, Copyright legislation, and the Promotion of Access to Information Act (PAIA). However, the content analysis of these legislation did not mention anything about the handling and management of digital collections. Technologies and equipment used in the digitisation process included high quality scanners, servers and hard drives with software such as Optical Character Recognition, Content document management software and the NLSA website. The challenges uncovered in the study in relation included duplication of digitisation efforts and lack of expertise in digitisation. This study recommends that given the evolution of technology, the NLSA should migrate to a more convenient cloud storage that has a large advantage in case of unlimited storage, and keep up to date with the trends of digitisation technology. Legislation governing the LIS in South Africa also needs amendment to cater for the handling and management of digital collections. v
Thesis (M.A. (Information Studies)) -- University of Limpopo, 2022
Keywords: Digital preservation; National library of South Africa; Documentary heritage; Collection development; Access; Libraries -- South Africa; Heritage tourism; Digital preservation; Library materials -- Digitization; Digital preservation